On the Methodology of Research of the Culture of Memory of the Post-socialist City (the Example of Contemporary Vilnius) - Kasner, Małgorzata (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English] The principal objective of this paper is to analyze the issue of the contemporary city and its memory. The end of the 20th century has brought an increased number of works on the memory of a city. This phenomenon has amplified the development of urban studies, architecture, geography and human studies as well. In this way, a so-called “spatial turn” took place. The “spatial turn” term refers to the change in thought of social and human scientists to the space that does not determine social action but provides a context for it. Space facilitates social action and creates a stimulus for social action to take place. Any city and its space have their own “language” speaking to us through their topographies, landscapes, architecture, art – anything that shapes the city’s aura and registers it in the memory culture. It can be reconstructed on the basis of various and rich urban representations. The fascinating and complex issue of a city’s memory in the postmodern age is a huge research challenge. In this context, the concept of transculturality, developed by Wolfgang Welsch, and all research achievements up to now are extremely inspiring. The examples collected by the author will illustrate possible research directions and useful scientific tools to conduct the analysis of Vilnius memory after 1990.